Financial Performance Innovation Since Digital Technology Entered Indonesian MSMEs - Maharini Adiandari, Ade (International Journal for Applied Information Management, 2022)
This study aimed to understand the accounting performance innovation of MSME business people since digital technology has become a business supporter. Before searching the data, we tried to understand the core of the problem, and then we searched the data with the help of electronically using keyword searches. Next, we will continue with the data studied by involving the data coding system to critically evaluate the interpretation of the data in-depth so that we conclude from the data that we harmonize with the meaning and intent of this research question. The data sources that we look at are some international journal publications that actively discuss financial and digital issues for Indonesian small businesses. The applications we mean are ah and France, Sage publications, Google books, emerald publications, and some websites that we visited to get data that could fill the discussion of this study. This study fully uses secondary data, namely data published by previous studies, and we report in a descriptive qualitative article under a phenomenological approach. This study system explores the data as comprehensively to understand a field of study, becoming valid and convincing data in answering and filling out the discussion. Based on the study data and discussion, we can summarize that many MSME drivers can still not apply digital technology in their financial system, which makes innovation in business implementation, especially financial reporting. Thus, this finding becomes a meaningful input in studying relevant themes in the future.